Youth and socialisation: relative behavior and perspective towards new media - Aboo Talib @ Khalid, Kartini; Shiratuddin, Norshuhada; Hassan, Shahizan; Abdul Rahman, Zainatul Shuhaida; Abdul Rahman, Nurul Labanihuda (Universiti Kebangsaan Malaysia, 2018)
This article examines marginalized youth and socialization process that result in relative behavior and perspective towards new media. Revolution 4.0 argues by Klaus Schwab analyzes that how rapid technological changes and society can coexist because the technology revolution demands the society to change in term of size, speed and scope. The question is, how youth with different socialization process would be prepared to face this technology revolution cum the utilization of social media? The changes are profound with full of promises but it also carries potential perils. The social construction process is needed to groom the marginalized youth to be technology savvy using social media on a daily basis. The relational theory, relativity behavior theory, socialization and social construction concept are applied to evaluate marginalized youths based on the five focus groups interviewed. Youths participations are voluntarily basis and samples are selected purposively among the youths of the age range between 15 to 24 years old. The results show that marginalized youths are skeptical towards new media and the explanation to such responses are socialization process, class, spatial, exposure and level of education are factors that triggered marginalized youths to be relationally different in their behavior and perspective from the Western concept of youth.